PRESENCE OF METATARSAL SYNDROME IN PATIENTS WITH HALLUX VALGUS DEFORMITY OPERATED BY KELLER'S METHOD - Georgieva, Daniela; Djoleva Tolevska, Roza; Nancheva, Jasminka; Georgiev, Antonio; Kamnar, Viktor; Atanasov, Nenad; Saveski, Aleksandar; Mirchevska Zogovska, Elizabeta (MIT Univerzitet Skopje, 2020)
Metatarsalgia syndrome is a common pathological outcome in patients with hallux valgus deformity. However, the association between the occurrence of preoperative and the presence or absence of postoperative metatarsalgia in operated patients with this deformity has not been systematically investigated. The aim of this study was to investigate the presence of metatarsal syndrome preoperatively and postoperatively in patients with hallux valgus deformity operated by resection arthroplasty using the Keller method. Material and method: The material of the study included 35 patients with hallux valgus deformity, treated with the operative procedure according to the Keller method. The metatarsal pain was evaluated with the clinical method - accordion test. Clinical and radiographic examination of the subjects was done preoperatively and postoperatively. Results: Metatarsalgia was registered before surgery in 27 (77.1%) subjects, of which only 5 (18.5%) subjects had this symptom after surgery. All 8 (22.9%) subjects without metatarsalgia preoperatively, are without this symptom and postoperatively. Conclusion: Resection arthroplasty according to Keller method allows a drastic percentage reduction of metatarsal syndrome in the postoperative period.